2021
DOI: 10.1089/whr.2020.0094
|View full text |Cite
|
Sign up to set email alerts
|

Travel, Treatment Choice, and Survival Among Breast Cancer Patients: A Population-Based Analysis

Abstract: Background: Travel distance to care facilities may shape urban-rural cancer survival disparities by creating barriers to specific treatments. Guideline-supported treatment options for women with early stage breast cancer involves considerations of breast conservation and travel burden: Mastectomy requires travel for surgery, whereas breast-conserving surgery (BCS) with adjuvant radiation therapy (RT) requires travel for both surgery and RT. This provides a unique opportunity to evaluate the impact of travel di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“… 53 The significantly longer travel times that people in remote localities within Victoria experienced to visit a COVID‐19 POCT site during the time in question could have hindered the use of such sites. An evidence‐based review conducted by Syed, Gerber and Sharp 54 confirmed that travel barriers – including distance – hinder health service use (subsequent to their review, this finding has been confirmed 55 ). Despite the severity of COVID‐19 and the recognition that swift response is needed, under the current context, people in rural and remote Victoria with poor proximate POCT site availability may have decided to forgo being tested.…”
Section: Discussionmentioning
confidence: 89%
“… 53 The significantly longer travel times that people in remote localities within Victoria experienced to visit a COVID‐19 POCT site during the time in question could have hindered the use of such sites. An evidence‐based review conducted by Syed, Gerber and Sharp 54 confirmed that travel barriers – including distance – hinder health service use (subsequent to their review, this finding has been confirmed 55 ). Despite the severity of COVID‐19 and the recognition that swift response is needed, under the current context, people in rural and remote Victoria with poor proximate POCT site availability may have decided to forgo being tested.…”
Section: Discussionmentioning
confidence: 89%
“…Rural patients diagnosed with DCIS were less likely than urban patients to receive PORT following BCS in our analysis and, during 1991/1995 only, significantly more likely to receive mastectomy than BCS. While previous research has identified geographic and rural–urban differences in treatment for patients diagnosed with early‐stage, invasive breast cancer, 14–19 this is the first large, population‐based study to characterize a recent 25‐year trend in locoregional treatment and evaluate differences between rural and urban DCIS patients. Previous studies evaluating rural–urban treatment differences have been sparse and limited by less recent time periods and smaller geographic regions 20–22 …”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Previous studies have reported significant differences in locoregional treatment patterns among patients diagnosed with invasive breast cancer by geographic region and across the rural-urban continuum. [14][15][16][17][18][19] However, few studies have evaluated whether such differences also exist among DCIS patients residing in rural versus urban areas. 12,[20][21][22] The purpose of this study was compare the type of cancer-directed surgery performed and use of PORT between rural and urban women diagnosed with DCIS between 1991 and 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel time and transportation difficulties have been established in multiple studies as barriers to radiotherapy for both definitive and palliative management. [15][16][17][18] Travel for radiotherapy was much less frequently reported as a barrier among respondents with onsite radiation oncology departments compared with those without onsite radiation departments (28% vs 71%, respectively; P < .001).…”
Section: Patient Travelmentioning
confidence: 99%